Parameter Identification for Micro Underwater Vehicles. Issue 1 (17th December 2018) - Duecker, Daniel Andre; Kreuzer, Edwin; Maerker, Gunnar; Solowjow, Eugen
Abstract: Detailed knowledge of model parameters is key for accurate forward simulations and control design. Identifying these parameters is especially challenging for underwater vehicles as they are subject to hydrodynamics effects which cannot be neglected in the equation of motion. In this work we present a method for hydrodynamic parameter identification of micro underwater vehicles which allow full‐size experiments due to their small size. The low‐cost experimental setup consists mainly on a free fall mass and an angular encoder. In an experimental series the hydrodynamic parameters of the micro underwater vehicle HippoCampus [1] are identified and compared with the analytically derived parameter set.